2001
DOI: 10.1093/nar/29.14.3099
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a novel hypoxanthine/xanthine dNTP pyrophosphatase from Methanococcus jannaschii

Abstract: A novel dNTP pyrophosphatase, Mj0226 from Methanococcus jannaschii, which catalyzes the hydrolysis of nucleoside triphosphates to the monophosphate and PPi, has been characterized. Mj0226 protein catalyzes hydrolysis of two major substrates, dITP and XTP, suggesting that the 6-keto group of hypoxanthine and xanthine is critical for interaction with the protein. Under optimal reaction conditions the k(ca)(t) /K(m) value for these substrates was approximately 10 000 times that with dATP. Neither endonuclease nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
0
38
1
Order By: Relevance
“…Our data suggest that RdgB is capable of efficiently hydrolyzing dHAPTP. Surprisingly, Chung et al have reported that Mj0226 displays a substrate specificity for dHAPTP that is at least 1,500-fold less than that for xanthine triphosphate (XTP), at least 1,000-fold less than that for dITP, and actually lower than that for dGTP (4). However, in our hands, the pyrophosphatase activity of RdgB against GTP can be significantly inhibited by addition of HAP to the reaction (unpublished results).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our data suggest that RdgB is capable of efficiently hydrolyzing dHAPTP. Surprisingly, Chung et al have reported that Mj0226 displays a substrate specificity for dHAPTP that is at least 1,500-fold less than that for xanthine triphosphate (XTP), at least 1,000-fold less than that for dITP, and actually lower than that for dGTP (4). However, in our hands, the pyrophosphatase activity of RdgB against GTP can be significantly inhibited by addition of HAP to the reaction (unpublished results).…”
Section: Discussionmentioning
confidence: 49%
“…The RecA protein plays a central role in homologous recombination and, in conjunction with the LexA protein, induces the SOS regulon in response to DNA damage (14,36,45). The RdgB protein, along with the human and Methanococcus jannaschii homologs, have been shown to have deoxyribonucleoside triphosphate pyrophosphatase activity on several purine base analog nucleotide triphosphates (4,34). Additionally, Clyman and Cunningham have shown that an rdgB mutant displays a hyperrecombinogenic phenotype and shows elevated levels of SOS expression.…”
mentioning
confidence: 99%
“…[1][2][3] These modifications often cause a nucleotide to pair with an alternate partner nucleotide in DNA. 4,5 For example, 8-oxo-dGTP, an oxidized product of dGTP, can pair with adenine as well as cytosine during replication, resulting in a transversion mutation. 4 8-Oxoguanine in DNA appears through two independent pathways, either by an incorporation of the oxidized precursor, 8-oxo-dGTP during DNA synthesis, or by the direct oxidation of a guanine base in DNA.…”
mentioning
confidence: 99%
“…Similarly, RdgB is the E. coli dITPase (10,14,15), whose function is to intercept the noncanonical DNA precursor dITP before hypoxanthine incorporates into DNA in place of guanine. If hypoxanthine forms within DNA by adenine deamination (36), endonuclease V initiates its removal (84,85).…”
mentioning
confidence: 99%